North Jakarta Aquarium Village Sanitation Case Study - Haryeni; Linda Handayuni; Barlian, Eri; Yuniarti, Elsa (Jurnal Kesehatan Cendikia Jenius, 2024)
The sanitation and environmental health conditions in coastal settlements, such as Kampung Aquarium in North Jakarta, have become a crucial issue in urban area management. This study aims to analyze the sanitation conditions and their impact on public health in the area. Using a qualitative approach with a case study method, data were collected through field observations, interviews, and documentation. Thematic analysis was employed to identify patterns and relationships among various sanitation aspects. The findings indicate that limited access to clean water, poor waste management systems, and a lack of environmental awareness are the primary factors contributing to sanitation problems. Conclusion: Limited sanitation, lack of access to clean water, and insufficient community awareness are the main health challenges in Kampung Aquarium. It is recommended that sanitation infrastructure be improved, community education programs be implemented, and a stronger collaboration between the government and the community be fostered to create a healthy environment.